Investigating The Internationalisation Of Malaysian Construction Firms Using The Integrated E3R Model - Wong , Sing Sing (2010)

(untitled)
As a WTO signatory, construction market in Malaysia has become more open to foreign construction firms. Malaysian CIDB has launched a master plan to drive the growth of the construction industry. Furthermore, the trend shows the increasing involvement of Malaysian construction firms in international markets. But limited studies have been conducted.Previous studies investigated the internationalisation of construction firms by applying a single theory. This study examines it with the integrated E3R Model.